Biblioteconomia e inteligência artificial (IA) novas possibilidades para o trabalho nas unidades de informação - MELO, Jéssica Lopes (2023)
The study addresses the topic of Artificial Intelligence (AI) in the context of Librarianship and Information Science. The objective is to get to know AI applications in information units and to raise the librarian's profile to work in a new technological scenario. The theoretical research is based on the principles of bibliographical and exploratory research. The results show that AI has potential for use in information retrieval systems and in virtual care provided by information units. Regarding skills, there is a need to update curricula so that future professionals have a more solid training in technology, being able to act as systems librarians or as data librarians. These specialties can offer possibilities for work on the use of AI. Finally, it is concluded that AI will increasingly become part of the routine in information units, which signals the search for librarian training capable of keeping up with the technological trends brought about by Industry 4.0.